Barriers and enablers to implementinghospital-acquired urinary tract infection prevention strategies: a qualitative study using the Theoretical Domains Framework. (July 2021) - Fasugba, O.; McInnes, E.; Baye, J.; Cheng, H.; Gordon, R.; Middleton, S.
Summary: Background: Consistent implementation of evidence-based hospital-acquired urinary tract infection (UTI) prevention strategies remains a challenge in acute and subacute care settings. Addressing the evidence–practice gap requires an understanding of factors affecting implementation of hospital-acquired UTI prevention strategies in this high-risk setting. Aim: To identify the perceived barriers and enablers of clinicians to implementing hospital-acquired UTI prevention strategies in an Australian subacute hospital. Methods: Qualitative semi-structured virtual interviews, underpinned by the Theoretical Domains Framework (TDF), were conducted with purposively selected nurses ( N = 8) and doctors ( N = 2) at one subacute metropolitan hospital. Interview data were content-analysed using the TDF as the coding framework. Findings: Eight TDF domains were identified as important in understanding barriers and enablers to implementing hospital-acquired UTI prevention strategies: Knowledge, Skills, Beliefs about capabilities, Emotion, Professional role and identity, Environmental context and resources, Goals, and Behavioural regulation. Barriers were poor awareness of clinical practice guidelines for hospital-acquired UTI prevention; lack of training; staff shortages; competing workloads; lack of procedural equipment for urinary catheterization; difficulty with implementing prevention strategies in cognitively impaired patients; language barriers; and lack of feedback and use of incident reporting data to influence clinical practice. Presence of a proactive staff culture and positive team approach to work emerged as enablers. Audit and feedback, clinical champions, education, and patient information resources in languages other than English were identified as potential enablers. Conclusion: The findings will inform development of theoretically informed behaviour change interventions to promote successful implementation of hospital-acquired UTI prevention strategies in the subacute setting.